Carrying Capacity for Sustainable Mariculture Development in The Dampier Strait Conservation Area, West Papua Province - Ichsan Suryo Wibowo Wibowo; Ali Mashar Mashar; Niken Tunjung Murti Pratiwi Pratiwi; Fery Kurniawan Kurniawan; Mazlan Mazlan (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2026)
The Dampier Strait Marine Conservation Area has the potential to be a location for the development of seaweed and pearl oyster cultivation. Despite the potential, there is no information on the limitations of space utilization capacity in implementing mariculture activities for both commodities. Therefore, this study aims to determine the carrying capacity of mariculture activities in the Dampier Strait Conservation Area using the Ecosystem Approach to Aquaculture (EAA) concept. The study procedures included ecological and production carrying capacity, which were analyzed using the physical capacity approach. The results revealed that the area with the potential to be developed for mariculture activities was 904.36 ha. In addition, the number of seaweed and pearl oyster units that could be developed was 1,282 units and 805 units, respectively, with annual production volumes of 8,076.60 tons of dry seaweed and 2,817,500 individual pearl oyster spats ready for operation. All stages of the analysis provided comprehensive results to achieve an optimal and sustainable utilization area from the development of mariculture activities. The analysis also considered the continuity between environmental potential and human demands in the use of ecosystem services in an integrated manner.